2007
DOI: 10.1002/gcc.20458
|View full text |Cite
|
Sign up to set email alerts
|

CRTC1/MAML2 fusion transcript in high grade mucoepidermoid carcinomas of salivary and thyroid glands and Warthin's tumors: Implications for histogenesis and biologic behavior

Abstract: We analyzed 55 primary salivary gland tumors including 22 mucoepidermoid carcinomas (MECs) to determine the association of MECT1/TORC1/CRTC1-MAML2 fusion transcript to tumor types, level of MEC differentiation and clinicopathologic parameters. Our primary salivary gland tumors were composed of 22 MECs, 11 Warthin's tumors, 10 adenoid cystic carcinomas, two basaloid carcinomas, five salivary duct carcinomas, and five adenocarcinomas, not otherwise specified. We also included, for the first time, three primary M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
183
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(206 citation statements)
references
References 54 publications
15
183
2
6
Order By: Relevance
“…Moreover, all low-grade tumors were positive for the CRTC1-MAML2 gene fusion, whereas only three of the 13 high-grade mucoepidermoid carcinomas were fusion-positive. 7,12,[19][20][21] The remaining 10 fusion-negative, high-grade tumors were also negative for the EWSR1-POU5F1 fusion previously identified in high-grade mucoepidermoid carcinomas. 22 These findings support the notion that low-grade mucoepidermoid carcinomas are fusion-positive and genetically stable tumors with few genomic imbalances.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, all low-grade tumors were positive for the CRTC1-MAML2 gene fusion, whereas only three of the 13 high-grade mucoepidermoid carcinomas were fusion-positive. 7,12,[19][20][21] The remaining 10 fusion-negative, high-grade tumors were also negative for the EWSR1-POU5F1 fusion previously identified in high-grade mucoepidermoid carcinomas. 22 These findings support the notion that low-grade mucoepidermoid carcinomas are fusion-positive and genetically stable tumors with few genomic imbalances.…”
Section: Discussionmentioning
confidence: 69%
“…17,18 Several studies have now confirmed the initial report by Behboudi et al 19 demonstrating that the CRTC1-MAML2 fusion primarily occurs in low-grade mucoepidermoid carcinomas with a favorable clinical outcome. 12,13,20,21 A second gene fusion involving the sarcoma-associated EWSR1 gene and the stem cell regulator POU5F1 was recently identified in mucoepidermoid carcinomas with a more immature morphology compared with MAML2 positive tumors. 22 Except for the CRTC1-MAML2 fusion, little is known about other genomic rearrangements of importance for the genesis and progression of mucoepidermoid carcinoma.…”
mentioning
confidence: 99%
“…The Crtc1-Maml2 fusion transcript was subsequently identified in primary thyroid, breast, cervix, lung and cutaneous sweat gland tumors with clear-cell, mucoepidermoid tumor-like histological features (Enlund et al, 2004;Behboudi et al, 2005;Kazakov et al, 2007;Tirado et al, 2007;Achcar et al, 2009;Camelo-Piragua et al, 2009;Kaye, 2009;Lennerz et al, 2009) unifying a group of tumors that arise from mucous/serous glands scattered throughout the body. As Crtc gene members are potent cAMP/CREB co-activators (Conkright et al, 2003;Iourgenko et al, 2003) and the ectopic expression of Crtc1-Maml2 activated a similar group of target genes (Coxon et al, 2005;Wu et al, 2005), a current model proposes that the fusion oncogene transforms cells by aberrantly co-activating specific Crtc1-inducible targets (Kaye, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the protein can be detected in tumors suggesting reactivation of dormant developmental gene. Although the incidence of this fusion in MEC varies, it is generally accepted that more than 50 % of this entity manifest the MECT1-MAML2 [13,16,17]. Fusion-positive cases showed significantly better survival than fusion-negative cases, suggesting that MECT1-MAML2 represents a specific prognostic molecular marker in MEC.…”
Section: T(11; 19) Mect-maml Fusion Transcript In Mecmentioning
confidence: 99%